The delinquent girl - Zahn, Margaret A. (Temple Univ. Press, 2009)
Introduction -- The contribution of "mainstream" theories to the explanation of female delinquency / Robert Agnew -- Feminist theories of girls' delinquency / Jody Miller and Christopher W. Mullins -- Trends in girls' delinquency and the gender gap: statistical assessment of diverse sources / Darrell Steffensmeier and Jennifer Schwartz -- Biopsychological factors, gender, and delinquency / Diana Fishbein, Shari Miller-Johnson, Donna Marie Winn, and Gayle Dakof -- Family influences on girls' delinquency / Candace Kruttschnitt, and Peggy Giordano -- Peer influences on girls' delinquency / Peggy Giordano -- Girls, schooling, and delinquency / Allison Ann Payne, Denise C. Gottfredson, and Candace Kruttschnitt -- Gender differences in neighborhood effects and delinquency / Margaret A. Zahn and Angela Browne -- The context of girls' violence: peer groups, families, schools, and communities / Merry Morash and Meda Chesney-Lind -- Young women and street gangs / Jody Miller -- Girls in the juvenile justice system / Barry C. Feld -- Appendix: Girls study group members -- References